Nano periodic structure forma-tion in 4H–SiC crystal using femtosecond laser double-pulses - Kim, E.; Shimotsuma, Y.; Sakakura, M.; Miura, K. (Сверхтвердые материалы, 2018)
The photo-induced periodic nano structure inside 4H–SiC have been induced by a femtosecond double pulse train. The alignment of the periodic structure is in the direction independently from crystal orientation. In particular, FE-SEM analysis revealed that the periodic structure on the fractured surface can be classified into two categories of the polarization-dependent and polarization-independent. Фотоіндукована періодична наноструктура всередині 4H–SiC була індукована фемтосекундним подвійним імпульсом. Вирівнювання періодичної структури відбувалося в напрямку, незалежному від орієнтації кристала. Зокрема, аналіз FE-SEM показав, що періодичну структуру на тріщинуватій поверхні можна розділити на дві категорії: поляризаційно-залежної та незалежної від поляризації. Фотоиндуцированная периодическая наноструктура внутри 4H–SiC была индуцированна фемтосекундным двойным импульсом. Выравнивание периодической структуры происходило в направлении, независимом от ориентации кристалла. В частности, анализ FE-SEM показал, что периодическую структуру на трещиноватой поверхности можно разделить на две категории: поляризационно-зависимой и независимой от поляризации.